Strategic Teaching in Inclusive EFL Classrooms : A Case Study on Reading Instruction for Dyslexic Students - Rosa Anjani; Ernita Daulay (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study explores teachers’ strategic teaching in supporting dyslexic students’ basic reading skills in Indonesian inclusive EFL classrooms, where evidence from authentic classroom practice remains limited. Using a qualitative case study design, the study investigates how an elementary school English teacher implements instructional strategies, adapts classroom practices, and addresses challenges in supporting dyslexic learners. Data were collected through semi-structured interviews, classroom observations, and document analysis. The findings indicate that the teacher employed multisensory phonics instruction, differentiated learning materials, and individualized scaffolding to facilitate students’ reading development. However, limited professional training, inadequate instructional resources, and time constraints remained significant challenges. These challenges were addressed through teacher initiative, including the development of low-cost instructional media and collaboration with parents. The study highlights the importance of teacher agency and adaptive instructional practices in supporting inclusive EFL reading instruction and provides practical implications for teachers working in resource-constrained inclusive classrooms.